Knowledge of Dietary Nutrition in Patients with Radiotherapy for Colorectal Cancer (KAP): A Descriptive Study - Wu, Huanhuan; Feliciano, Evelyn E. (International Journal of Public Health and Medical Research, 2025)
Objective: To investigate the status quo of dietary nutrition knowledge, belief and behaviors of patients with colorectal cancer undergoing radiotherapy, and to analyze its influencing factors, so as to provide basis for clinical nutrition management. Methods: a convenient sampling method was used to select 200 patients with colorectal cancer who received radiotherapy in the oncology department of three Grade A hospitals in Binzhou City from January to May 2024 for related study. A questionnaire survey was conducted on the knowledge, belief and behavior of total nutrition management of the respondents. In addition, demographic and clinical factors that may affect KABP in hospitalized patients with radiotherapy were investigated and analyzed, so as to provide a basis for formulating nutritional management measures for hospitalized patients with colorectal cancer with radiotherapy in clinical work. Results: The results showed that the average score of nutritional knowledge was 5.03±4.04, and the passing rate was 24.53%. The average score of nutrition attitude was 27.78±5.90, the pass rate was 80.19%; The average score of nutrition behavior was 29.05±8.86, and the pass rate was 18.4%. Age, sex, family residence, education level, occupation, family monthly income, type of medical insurance, type of radiotherapy and whether or not concurrent chemotherapy had significant differences in the total score of dietary nutrition knowledge and practice of patients with colorectal cancer inpatient radiotherapy. Discussion: This study showed that inpatients with radiotherapy for colorectal cancer had insufficient dietary nutrition knowledge reserve and poor nutritional behavior, but positive attitude towards nutrition. Gender, family per capita monthly income, family location and treatment were the main factors affecting the knowledge and practice of dietary nutrition in patients with colorectal cancer radiotherapy, especially the family residence, which had the greatest influence.